Use of live food as starter diet in feed training juvenile pirarucu - Cavero, Bruno Adan Sagratzki; Ituassú, Daniel Rabelo; Filho, Manoel Pereira; Roubach, Rodrigo; Bordinhon, André Moreira; Fonseca, Flávio Augusto Leão da; Ono, Eduardo Akifumi (Pesquisa Agropecuaria Brasileira, 2003)
In this trial, two different live foods were tested as starter diet in the feed training of juvenile pirarucu, Arapaima gigas. Two treatments were used, Artemia sp. and a mixture of native zooplankton. Weight gain, percentage of feeders and survival did not show any difference between treatments (p > 0.05). Live food is efficient as starter diet to train juvenile pirarucu to accept dry feed.
Keywords: Arapaima gigas; fish feeding; fishery